Effect of Feedback on the Performance of Secondary School Students in Mathematics in Ekiti State. - Olofinlae, O.O (IJRDO- Journal of Educational Research, 2020)
The study focused on the effect of feedback on the performance of Senior Secondary School Students in mathematics in Ekiti State. It employed a quasi-experimental research design of pre-test and post-test type. The population of the study consisted of all Senior Secondary School Two (SSS2) students in Ado Local Government Area of Ekiti State. A sample of one hundred (100) SSS2 students was selected from four secondary schools using a multi-stage random sampling technique. The instrument for data collection consisted of self-structured Students Mathematics Performance Test (SMPT) whose reliability coefficient was obtained as 0.74 using Pearson Product Moment Correlation Coefficient (PPMC). Three research hypotheses were formulated and tested using t-test statistic at the α=0.05 level of significance. Findings revealed that there was no significant difference between the mean performance scores of students who were provided feedbacks and those without feedbacks in mathematics pre-test. However, a significant difference existed between the mean performance scores of students who were provided feedbacks and those without feedbacks in mathematics post-test, attributable to the treatment. It was recommended that feedback should be provided for students to aid their performance.